2015
DOI: 10.1038/srep15212
|View full text |Cite
|
Sign up to set email alerts
|

EGR1 regulates hepatic clock gene amplitude by activating Per1 transcription

Abstract: The mammalian clock system is composed of a master clock and peripheral clocks. At the molecular level, the rhythm-generating mechanism is controlled by a molecular clock composed of positive and negative feedback loops. However, the underlying mechanisms for molecular clock regulation that affect circadian clock function remain unclear. Here, we show that Egr1 (early growth response 1), an early growth response gene, is expressed in mouse liver in a circadian manner. Consistently, Egr1 is transactivated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…We observed a pronounced daily rhythm in per2, npas2 and egr1 expression in the liver with the maximum as was reported before (Damiola et al 2000, Tao et al 2015. per2 and npas2 expression was not influenced by food reward; however, food reward caused a diminishing of egr1 rhythmic expression.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…We observed a pronounced daily rhythm in per2, npas2 and egr1 expression in the liver with the maximum as was reported before (Damiola et al 2000, Tao et al 2015. per2 and npas2 expression was not influenced by food reward; however, food reward caused a diminishing of egr1 rhythmic expression.…”
supporting
confidence: 86%
“…per2 and npas2 expression was not influenced by food reward; however, food reward caused a diminishing of egr1 rhythmic expression. Food reward with food restriction caused a pronounced phase shift in gene expression as was reported earlier (Damiola et al 2000, Tao et al 2015.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…4b ). Egr1 and members of the Klf family are known to participate in biorhythm regulation 55 58 , e. g., Egr1 can regulate the clock gene Cry1 55 , the key repressor gene that can propel the animal into sleep phase (through the inhibition of key activators Clock and Bmal1 59 ). We therefore investigated the expression patterns of clock-related genes during the aestivation of sea cucumber.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that the REV-ERBα expression leading to apoptosis was affected by circadian rhythms ( 22 ). REV-ERBα controls the circadian clock genes and regulates Early growth response 1 expression, causing extensive expression of Tumor protein p73 (p73) ( 23 ). p73 activates the transcription of Bax and Bcl-2, causing the release of cytochrome c from the mitochondria ( 24 ).…”
Section: Discussionmentioning
confidence: 99%